Progress in Convergent Paired Electrolysis. Issue 47 (4th July 2022) - Zhang, Sheng; Findlater, Michael
Abstract: Convergent paired electrolysis combines both anodic and cathodic reactions simultaneously in an electrochemical transformation. It provides a highly energy‐efficient and divergent approach to conventionally challenging and useful structures. However, the physical separation of the two half‐electrode reactions makes it extremely difficult to couple the intermediates arising from the two electrodes. In this concept article, four strategies used in convergent paired electrolysis will be discussed from the perspective of the reaction mechanism: a) metal‐catalyzed convergent paired electrolysis, b) convergent paired electrolysis enabled by persistent radical effects, c) microfluidic chemistry applied to convergent paired electrolysis, and d) alternating current electrolysis. Abstract : Recent progress on convergent paired electrolysis has been summarized in this concept article. Four strategies based upon metal catalysis, persistent radical effects, microfluidic chemistry, and alternating current electrolysis are discussed in relation to their underlying mechanisms.